Nudging in Public Health Lifestyle Interventions: A Systematic Literature Review and Metasynthesis. (October 2020) - Ledderer, Loni; Kjær, Marianne; Madsen, Emilie Kirstine; Busch, Jacob; Fage-Butler, Antoinette
Nudging is increasingly used in public health interventions in Western societies to produced health-promoting behavior changes; however, there is lack of clarity as to what constitutes a nudge, scant knowledge of the effectiveness of nudging techniques in public health lifestyle interventions and a number of ethical and value-based concerns. The aim of this review is to address these research lacunae and identify the characteristics of nudges in empirical research on public health interventions intended to induce healthy lifestyle changes, including whether they are effective. We conducted systematic searches for relevant articles published between January 2008 and April 2019 in three databases, PubMed, CINAHL and PsycINFO, and combined this with a metasynthesis to construct interpretative explanations. A total of 66 original studies met the inclusion criteria. The findings of the systematic review showed that most nudging interventions involved diet/nutrition, most were carried out as single experiments, and the majority had the intended effects. Specific nudging techniques were identified with respect to the broader nudging categories of accessibility, presentation, using messages and pictures, technology-supported information, financial incentives, affecting the senses, and cognitive loading; several studies included more than one nudging technique. Although many nudging techniques had the intended effects, it is unclear whether they would work outside the study setting. The synthesis revealed that the studies lacked critical reflection on the assumptions about health that were implicit in nudging interventions, the cultural acceptability of nudges, the context-free assumptions of nudging theory, and the implications of these aspects for the public health context.